Ramayana for Piano - Trakulhun, Wiboon (Rangsit Music Journal, 2022)
Ramayana is a programmatic composition for piano solo in which articulates the character Ramasoon’s events of great importance to the storyline of the Thai literature Ramayana. The composition is 17 minutes in length that is comprised of 2 movements corresponding to the events to which Ramasoon is present in the literature. The composition’s raw materials originate from the pentatonic scale, symmetrical scale, synthetic scale, and cluster chord. Moreover, the composition uses Richard Wagner’s composition idea, particularly on the leitmotif which insinuates the leading motives that convey Ramasoon, Mekhala, and Phra Rama’s characters. Furthermore, the whole-tone scale, French augmented sixth chord, and diminished seventh chord expresses the two incidents aforementioned, which this scale and chords communally retain tri-tone intervals. The composition also contains quartal and quintal chords, and symmetrical set (027). This composition is in neo-tonality, however also uses bitonality and polychord, including Thai traditional pieces namely, Choed Ching and Choed Jin.